1993
DOI: 10.1111/j.1749-7345.1993.tb00001.x
|View full text |Cite
|
Sign up to set email alerts
|

Larval Nutritional Physiology: Studies with Clarias gariepinus, Coregonus lavaretus and Scophthalmus maximus

Abstract: Studies on the nutritional physiology of larval fish should provide the basis for defining the length of the larval period and for understanding the quantitative and the qualitative feed requirements of the larvae. For these purposes, it is necessary to perform both descriptive investigations on the ontogenesis of structures and functions as well as experimental investigations on adaptive strategies of the larvae under changing feeding regimes. In the present communication, examples of both approaches are disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
78
0
11

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(91 citation statements)
references
References 45 publications
2
78
0
11
Order By: Relevance
“…Enzymes related to metabolism (digestion, absorption and transport) of proteins, lipids and carbohydrates from the egg and yolk reserves have been detected following fertilization and immediately after hatching [55][56][57][58].…”
Section: Discussionmentioning
confidence: 99%
“…Enzymes related to metabolism (digestion, absorption and transport) of proteins, lipids and carbohydrates from the egg and yolk reserves have been detected following fertilization and immediately after hatching [55][56][57][58].…”
Section: Discussionmentioning
confidence: 99%
“…Fontagne, et al, (1998) observed in common carp, that due to deficiency of dietary phospholipid, resulting an increase in height of mucosal epithelium, a reduced total liver volume, mean hepatocyte volume and an accumulation of fat droplets in the enterocytes of the anterior intestine. A reduction of the enterocyte height has been used as an indicator of starvation in larvae (Segner et al, 1993;McFadzen et al, 1994;Theilacker and Watanabe, 1989). Regarding the good growth of carp larvae fed Artemia or phosphatidylcholine-enriched diets (Geurden et al, 1998), result showed the decrease of enterocyte height was not due to underfeeding conditions, and it might be because of active lipid absorption with diffuse appearance.…”
Section: Histoarchitecture Of the Intestine Of L Vannameimentioning
confidence: 99%
“…In C. gariepinus, it has been reported that although larvae were able to be reared on microdiets from the onset of exogenous feeding, their growth rates were not comparable to those fed live food until their stomach became functional (Verreth and van Tongeren 1989;Verreth et al, 1992). Therefore, the larval period in terms of nutrition ends with the completion of a functional stomach (Segner et al, 1993), and consequently, the stomach differentiation is considered as a decisive event in the nutritional physiology of larvae and could be used as an external marker for the start of weaning (Verreth et al, 1992;Senger et al, 1993).…”
Section: Resultsmentioning
confidence: 99%